A review of the mechanical properties of beetle elytra and development of the biomimetic honeycomb plates. (July 2015) - He, Chenglin; Zu, Qiao; Chen, Jinxiang; Noori, Mohammad N
This paper reviews the mechanical properties of beetle elytra. (1) The elytra has a lightweight border frame structure and has an optimal design, which includes variable cross-sections suitable for different positions and enables the required moment of inertia needed for flight. (2) Due to the non-equiangular, laminated structure of the elytra, there are two types of tensile fracture morphologies: fiber breakage and residual bridging. This study demonstrates the anisotropy and the effectiveness of the elytra's tensile strength by analyzing the orientations of the fibers. (3) The trabecular structure can be used to efficiently improve the peel resistance of the laminated composites, and its three-dimensional strengthening mechanisms have been clarified. (4) A mystery contained in the beetle elytron structures and its biological meanings are revealed, and a biomimetic application example is given. Based on the above points, possible directions for future work are also indicated in this paper.